The Mediating Role of Ambidextrous Learning Between Entrepreneurial Orientation and Business Performance on Women Entrepreneurs - Denta Felli Ananda; Ilone Shantia Gultom (UNIVERSITAS NEGERI SURABAYA, 2026)
Objective: The study explores the impact of innovativeness, proactiveness, and risk taking on the business performance of women entrepreneurs within the Jabodetabek region through ambidextrous learning. Method: A quantitative approach with Structural Equation Model (SEM-PLS) data from 110 women entrepreneurs in Jabodetabek which used a purposive sampling technique indicates that innovativeness not only increase ambidextrous learning, it also directly increases business performance. Proactiveness both directly enhances ambidextrous learning and business performance. Risk taking also proven increasing on both ambidextrous learning and business performance. Results: Research findings also highlight the role of ambidextrous learning as a mediating role. It effectively mediates the impact of innovativeness, proactiveness, and risk taking on business outcomes. Novelty: The outcome of this research offers valuable contribution to practical insight of ambidextrous capabilities to optimize entrepreneurial orientation dimensions, enabling women entrepreneurs to enhance adaptability, drive growth, and achieve sustained business success in dynamic market environments.